Shock Index, Pediatric Age-Adjusted Predicts Morbidity and Mortality in Children Admitted to the Intensive Care Unit - Huang, Kuo-Chen; Yang, Ying; Li, Chao-Jui; Cheng, Fu-Jen; Huang, Ying-Hsien; Chuang, Po-Chun; Chiu, I-Min (Frontiers in Pediatrics, 2021)
Background: Shock index, pediatric age-adjusted (SIPA), defined as the maximum normal heart rate divided by the minimum normal systolic blood pressure by age, can help predict the risk of morbidity and mortality after pediatric trauma. Methods: This multicenter retrospective study enrolled non-traumatic patients aged 1–17 years who presented to the pediatric emergency department (ED) and were directly admitted to intensive care unit (ICU) from January 1, 2016, to December 31, 2018, in Taiwan. SIPA was calculated at the time of arrival at the ED and 24 hours after ICU admission. Cutoffs included SIPA >1.2 (patient age: 1–6), >1.0 (patient age: 7–12), and >0.9 (patient age: 12–17). The utility of SIPA and the trends in SIPA during the first 24 hours of ICU admission were analyzed to predict outcomes. Results: In total, 1,732 patients were included. Of these, 1,050 (60.6%) were of preschool age, and the median Pediatric Risk of Mortality score was 7 (5–10). In total, 4.7% of the patients died, while 12.9% of the patients received mechanical ventilator support and 11.1% of the patients had profound shock episodes. SIPA at 24 hours after admission was associated with increased mortality (odds ratio [OR]: 4.366, 95% confidence interval [CI]: 2.392–7.969, p<0.001), mechanical ventilator (MV) support (OR: 1.826, 95% CI: 1.322–2.521, p<0.001), shock (OR: 2.306, 95% CI: 1.599–3.326, p<0.001), and longer hospital length of stay (HLOS) (2.903 days, 95% CI: 1.734–4.271, p<0.001). Persistent abnormal SIPA was associated with increased mortality (OR: 2.799, 95% CI: 1.566–5.001, p=0.001), MV support (OR: 1.457, 95% CI: 1.015–2.092, p=0.041), shock (OR: 1.875, 95% CI: 1.287–2.833, p=0.001), and longer HLOS (3.2 days, 95% CI: 1.9–4.6, p<0.001). Patients with abnormal to normal SIPA were associated with decreased mortality (OR: 0.258, 95% CI: 0.106–0.627, p=0.003), while patients with normal to abnormal SIPA were associated with increased mortality (OR: 3.055, 95% CI: 1.472–5.930, p=0.002). Conclusions: In non-traumatic children admitted to the ICU from the ED, increased SIPA at 24 hours after ICU admission predicted higher mortality and worse outcomes. Monitoring the trends in SIPA could help with prognostication and optimize early management.